'We teach, we record, we edit, and we reflect': Engaging pre-service language teachers in video-based reflective practice. (May 2022) - Yuan, Rui; Mak, Pauline; Yang, Min
The significance of reflective practice (RP) has been widely recognized in both general education and language education. The past years have witnessed an exponential growth of studies in examining how technology can be utilized to promote teachers' RP and video-based RP has been extensively reported as a powerful tool for teacher learning in many educational contexts. While existing literature has documented the potential benefits that student teachers may reap from video-based RP, there is a lack of attention to the complex interplay between the process of their RP and the contextual factors in their situated learning environment. This article reports on a study which aims to promote video-based RP among student teachers in a pre-service language teacher education course in Hong Kong. Drawing on data from post-course interviews with and the videoed reflection of six student teachers, the study uncovered the complex and dynamic process of the student teachers' video-based RP. This article offers practical implications for language teachers, teacher educators and school leaders on how to promote RP in second language teacher education.